Does science promote women? Evidence from academia 1973-2001 - National Bureau of Economic Research, Cambridge; Ginther, Donna K.; Kahn, Shulamit (Cambridge, MA, 2006)
"Many studies have shown that women are under-represented in tenured ranks in the sciences. We